PENGARUH HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MEREK LIFEBUOY DI KOTA BANJARMASIN - Nur Ghina Annisa Rahmah; M. Hasanur Arifin; Rizky Muslim Hidayat; Humaidi (Smart Business Journal (SBJ), 2023)
This study aims to investigate the effects of price and brand image on the purchase decision of the Lifebuoy brand in Banjarmasin City. The research method used in this study is a quantitative research method using a sample of 136 respondent of Lifebuoy Brand consumers. The data collection technique used in this study was to use a questionnaire and sampling using Acidental sampling. The analysis technique used in this research are multiple linear regression model, T test, F test and coefficient of determination test. The results of the T test for the price variable obtained a significance value of 0.000<0.05 and the brand image variable obtained a significance value of 0.000<0,05. Based on the results of the T test, it can be concluded that price and brand image affect purchasing decisions. The results of the F test has a significance value of 0.000 <0.05. The results showed that simultaneously price and brand image had an affect on purchasing decisions. The coefficient of determination (R2) is 0.522 or 52,2% consumer purchasing decisons are influenced by price and brand image. While 47,8% is influenced by other variables outside of this study.